Desire in Paul's undisputed epistles: semantic observations on the use of epithymeō, ho epithymētēs, and epithymía in Roman imperial texts - Bowden, Andrew M. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2020)
Cover -- Titel -- Acknowledgments -- Preface -- Table of Contents -- Abbreviations -- Part I. Introduction to ἐπιθυμέω, ἐπιθυμητής, and ἐπιθυμία in Roman Imperial Texts and in the Undisputed Epistles of Paul -- Chapter 1: History of Research on ἐπιθυμέω κτλ in the Undisputed Pauline Epistles Published over the Past Eighty Years -- 1.1 Friedrich Büchsel and Paul Wilpert on ἐπιθυμέω κτλ in Paul and in Relation to other Greco-Roman Philosophies and Religions -- 1.2 ἐπιθυμία κτλ in Romans 7 Alludes to the Command in Gen 3 -- 1.3 ἐπιθυμία κτλ Relates to Sexual Activity -- 1.3.1 William. D. Davies and Daniel Boyarin: ἐπιθυμία κτλ as יצר הרע and in Relation to Sexual Activity -- 1.3.2 Kathy L. Gaca: ἐπιθυμία κτλ in Relation to Sexual Activity -- 1.3.3 Jennifer W. Knust: ἐπιθυμία κτλ in Relation to Sexual Activity -- 1.4 David Fredrickson's Eros and the Christ: Longing and Envy in Paul's Christology -- 1.5 Stanley Stowers's and Emma Wasserman's Interpretation of ἐπιθυμία κτλ in Paul's epistle to the Romans -- 1.6 Semantic Observations Regarding ἐπιθυμία κτλ in the Roman Empire and in Paul -- Chapter 2: Semantic Observations on the Use of ἐπιθυμέω κτλ in Roman Imperial Texts -- 2.1 Applying John Lyons's Theory of Semantic Analysis to ἐπιθυμέω κτλ in Roman Imperial Texts -- 2.2 Previous Lexicons and Dictionary Entries in Relation to Louw and Nida (1988) -- 2.2.1 Lexicons of Ancient Greek before 1988 -- 2.2.2 Lexicons of Ancient Greek after 1988 -- 2.2.3 ἐπιθυμέω κτλ in Louw and Nida (1988) and in Antiquity -- 2.3 A Consideration of Philo's De decalogo to Better Understand the Sense Relations and Denotations of ἐπιθυμέω and ἐπιθυμία in the Roman Empire -- 2.4 The Sense Relations of ἐπιθυμέω κτλ in Roman Imperial Texts -- 2.4.1 The Paradigmatic Sense Relations -- 2.4.2 The Syntagmatic Sense Relations -- 2.4.2.1 ἐπιθυμία κτλ for ἡδονή κτλ.